Species assemblages of ladybirds including the harlequin ladybird Harmonia axyridis: a comparison at large spatial scale in urban habitats - Viglášová, Sandra; Nedvěd, Oldřich; Zach, Peter; Kulfan, Ján; Parák, Michal; Honěk, Alois; Martinková, Zdenka; Roy, Helen E. (BioControl (Dordrecht, Netherlands), 2017)
We evaluated the status of native ladybird assemblages in the presence of the non-native ladybird Harmonia axyridis Pallas (Coleoptera: Coccinellidae) in three European countries. To achieve this, we assessed the abundance of ladybirds from common host plants in urban areas of Great Britain, Czech Republic and Slovak Republic in 2014. We determined (i) the effects of season, host plant, location, abundance of H. axyridis and aphids on the ladybird species assemblage, (ii) the relationship between ladybird abundance and aphid density, (iii) the relationship between diversity of native ladybird species and the abundance of H. axyridis . There was a non-linear relationship between abundance of ladybirds and abundance of aphids but we found the abundance of other ladybird species was not correlated with H. axyridis . We highlight the value of large-spatial scale studies for revealing patterns in community assemblages and ultimately informing understanding of ecosystem resilience.